"The IR is a Nice Thing But...": Attitudes and Perceptions of the Institutional Repository - Doro, Nicole (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2021)
What attitudes and perceptions do faculty members, graduate students, and other stakeholders have regarding the institutional repository (IR)? I conducted a study at the University of Western Ontario through a survey of 316 participants from various faculties and in roles ranging from graduate students to tenured faculty members, followed by interviews with 10 faculty members and 3 librarians to discuss aggregate results from the survey. Results suggest a course of action for librarians who work with IRs, based on participants’ perceptions of barriers to use (branding, data ownership, resistance to open access (OA), alternative avenues for self-archiving) and elements of the IR participants enjoy and find motivating for use (continued access for graduates, dissertations and theses, pre-print literature reviews, satisfying OA mandates). Suggested next steps to promote IR uptake cover a number of different areas: mediated deposit; clarify benefits for faculty members; communication between library and users; opt-in features; tenure and promotion; enforcing OA mandates; and collaboration.